Ecological and Socio-Economic Modeling of Consequences of Biological Management Scenarios Implementation in Integrated Watershed Management (Case Study: Simindasht Catchment) - A. R. Keshtkar; H. Naseri (Iranian Journal of Applied Ecology, 2016)
Integrated watershed management is considered as a new principle for development planning and management of water and soil resources emphasizing on socio-economic characteristics of the region to sustainable livelihoods without vulnerability for plants and the residents of an area. This research, in line with the objectives of integrated management, has been carried out for modelling and evaluating the effects of ecological, socio-economic consequences resulting from the implementation of the proposed management plans on the vegetation changes with a focus on the problems in Simindasht catchment, located in Semnan and Tehran Provinces. After standardization of indices by distance method and weighing them, the scenarios were prioritized using multi-criteria decision-making technique. Trade-off analysis of the results indicates that in the integrated management of Simindasht catchment more than one single management solution, covering all aspects of the system can be recommended in different weighting approaches. The approach used herein, considering the results of different models and comparing the results, is an efficient tool to represent the watershed system as a whole and to facilitate decision making for integrated watershed management.